Essays on Near Eastern Art and Archaeology in Honor of Charles Kyrle Wilkinson - Prudence O. Harper (1983)
Proceedings of a symposium held at the MMA, 23 February 1981. Foreword by Vaughn E. Crawford; p. 9-10: Laudatio by P. O. Harper; p. 11-12: A selected bibliography of works by Ch. K. Wilkinson.